Hospital at home for acute medical illness: The 21st century acute medical unit for a changing population. (24th November 2021) - Knight, Thomas; Lasserson, Daniel
Abstract: Recent trends across Europe show a year‐on‐year increase in the number of patients with acute medical illnesses presenting to hospitals, yet there are no plans for a substantial expansion in acute hospital infrastructure or staffing to address demand. Strategies to meet increasing demand need to consider the fact that there is limited capacity in acute hospitals and focus on new care models in both hospital and community settings. Increasing the efficiency of acute hospital provision by reducing the length of stay entails supporting acute ambulatory care, where patients receive daily acute care interventions but do not stay overnight in the hospitals. This approach may entail daily transfer between home and an acute setting for ongoing treatment, which is unsuitable for some patients living with frailty. Acute hospital at home (HaH) is a care model which, thanks to advances in point of care diagnostic capability, can provide a credible model of acute medical assessment and treatment without the need for hospital transfer. Investment and training to support scaling up of HaH are key strategic aims for integrated healthcare systems. Abstract : Content List – This is an article from the symposium: "When is too much too much and too little too little: Scientific evidence of limited workup".